2015
DOI: 10.1093/jpids/piv035
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of First-Line Antituberculosis Drugs Using WHO Revised Dosage in Children With Tuberculosis With and Without HIV Coinfection

Abstract: The revised dosages appeared to be adequate for isoniazid and pyrazinamide, but not for rifampin or ethambutol in this population. Higher dosages of rifampin and ethambutol than currently recommended may be required in most children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 24 publications
4
30
1
Order By: Relevance
“…Pharmacokinetic (PK) sampling was performed at or after 4 weeks of anti-TB treatment as previously described (36). At the time of sampling, none of the HIV-coinfected patients were on antiretroviral therapy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacokinetic (PK) sampling was performed at or after 4 weeks of anti-TB treatment as previously described (36). At the time of sampling, none of the HIV-coinfected patients were on antiretroviral therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Drug concentrations were determined using validated liquid chromatography-tandem mass spectrometry (LC-MS/MS) methods as we previously described (36). The observed C max and time to C max (T max ) were determined by inspection of the serum concentration-time graphs for each drug.…”
Section: Methodsmentioning
confidence: 99%
“…Drug concentrations were determined at the pharmacology laboratory at the University of Cape Town using validated liquid chromatography-mass spectrometry methods. The methods were validated over the concentration ranges of 0.0977 to 26.0 g/ml for isoniazid, 0.117 to 30.0 g/ml for rifampin, 0.200 to 80.0 g/ml for pyrazinamide, and 0.0844 to 5.46 g/ml for ethambutol (20). All samples that were below the level of quantification (BLQ) were set to half of the lower limit of quantification (LLOQ).…”
Section: Methodsmentioning
confidence: 99%
“…TB remains a major cause of childhood mortality in areas where TB is endemic [78,79]. Treatment of childhood TB is particularly challenging because dosing recommendations have been largely derived from schedules employed for adults with a relative lack of supportive data on pharmacokinetics (PK), efficacy, and safety of the anti-TB agents in pediatric patients [80,81].…”
Section: Pediatric Patientsmentioning
confidence: 99%
“…Previously, recommended dosages for the first-line anti-TB drugs in children, expressed in milligram per kilogram body weight, were the same as for adults. However, several studies reported lowplasma concentrations of the first-line anti-TB drugs due to underdosing in children [79]. Consequently, in 2010, WHO recommended increased pediatric dosages for isoniazid (7-15 mg/kg), rifampicin (10-20 mg/kg), pyrazinamide (30-40 mg/kg), and ethambutol (15-25 mg/kg), which are higher than the adult recommended dosages (4-6, 8-12, 20-30, and 15-20 mg/kg, respectively) [2].…”
Section: Pediatric Patientsmentioning
confidence: 99%